Modified Great Toe Wraparound Flap with Preservation of Plantar Triangular Flap for Reconstruction of Degloving Injuries of the Thumb and Fingers: Long-Term Follow-Up. Issue 1 (July 2016) - Shen, Xiao Fang; Mi, Jing Yi; Xue, Ming Yu; Zhao, Gang; Qiang, Li; Zhou, Xiao; Rui, Yong Jun; Chim, Harvey
Abstract : Background: The purpose of this article is to report the authors' experience with the use of the modified great toe wraparound flap with preservation of a plantar triangular flap for reconstructing degloving injuries of the thumb and fingers. Methods: Between 2007 and 2012, 31 patients underwent reconstruction with 37 flaps. Twenty-seven patients underwent reconstruction with 31 flaps for a degloved thumb and fingers, and four patients underwent reconstruction with six flaps for degloved fingers only. A modified great toe wraparound flap with second toe medial toe hemipulp flap on a common pedicle was used for reconstruction of degloved fingers in four patients. Twelve patients had long-term follow-up, with a mean duration of 5 years (range, 2 to 8 years). Results: All flaps survived. The contour of the reconstructed digits was similar to the contralateral one. In patients with long-term follow-up, mean two-point discrimination of reconstructed digits was 6.2 mm (range, 3 to 8 mm). Mean Disabilities of the Arm, Shoulder and Hand questionnaire score was 0.8 ± 1.0. Mean Michigan Hand Outcomes Questionnaire score was 87.3 ± 3.7. Mean Foot and Ankle Disability Index score was 95.5 ± 2.7. The width of the preserved plantar triangular flap expanded from 35 percent to 67 percent of the width of the great toe and completely covered the weight-bearing area. Conclusions: Reconstruction of degloved thumb and fingers with a modified great toe wraparound flap, preserving a plantar triangular flap, results in excellent contour and functional outcome. Donor-site morbidity in the foot was minimal. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.